Volume guarantee ventilation in the weaning phase of preterm infants - Mohamed T. Khashaba; Mohamed M. El-Mazahi; Nehad A. Nasef; Mohamed Abdel Salam; Naglaa A. Moussa (SpringerOpen, 2015)
Background: Weaning from mechanical ventilation is a dynamic process influenced by many factors. Volume guarantee is a new option within the patient-triggered modes of ventilation and it can be best described as pressure-limited, continuous flow ventilation with tidal volume guidance or tidal volume targeting. Objectives: The aim was to assess whether volume guarantee (VG) added before presumed window time of 48 h pre-extubation can help to significantly shorten this window in infants with respiratory distress syndrome (RDS). Patients and methods: This study was conducted at Al-Azhar University (Damietta, NICU of Pediatric Department) in collaboration with Mansoura Faculty of Medicine, Egypt, between January 2012 and January 2013. Forty ventilated babies were randomly assigned during weaning phase to either VG (group 1) (10 SIMV + VG & 10 PSV + VG); or no VG group 2 (10 SIMV & 10 PSV). All babies were ventilated by Drager Babylog 8000 ventilator due to respiratory distress syndrome (AC or SIMV as initial mode). Results: Infants randomized to VG group achieved weaning success criteria faster than those randomized to no VG group. Adding VG at the weaning phase resulted in more stable TV, a significant decrease in the mean airway pressure (MAP), oxygenation index, weaning duration, post extubation NCPAP duration and extubation failure. No statistically significant differences were observed in the incidence of pneumothorax, patent ductus arteriosus (PDA), bronchopulmonary dysplasia (BPD), weight gain and neonatal sepsis. Conclusion: Volume guarantee seems to be both safe and effective in this group of patients.